The state of wellbeing education across North American medical schools: A scoping review - Raiter, Noam; Yau, Kiana; Sharma, Alisha; Lewis, Melanie; Do, Victor (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2024)
Background/Objective: Medical students experience increased rates of burnout and mental illness compared to the general population. Yet, it is unclear to what extent North American medical schools have adopted formal wellbeing curricula. We sought to establish prevailing themes of existing wellbeing educational interventions to identify opportunities for further curricular development.Methods: We conducted a scoping review of the literature searching for wellbeing education programs implemented for undergraduate medical students across North America. We searched four comprehensive databases and grey literature and only included published original research. Two independent researchers screened all papers with a third to resolve any disagreements. Two researchers conducted the data extraction following a predetermined template that was refined continuously, with a third researcher to resolve any discrepancies.Results: We identified 3996 articles in the initial search of which 30 met inclusion criteria and were included for further analysis. The most common types of interventions were mindfulness and meditation practices. 27 studies found that their wellbeing sessions contributed to positive wellbeing outcomes of learners.Conclusions: Our review identified that there are few wellbeing curricular initiatives that have been evaluated and published in the literature. Additionally, the methodology and rigour of wellbeing curriculum evaluation to date leaves significant room for improvement. The existing literature does suggest that the adoption of a wellbeing curriculum has the potential to improve outcomes for medical students. These findings can be used to assist the development of a validated wellbeing curricular framework for wellbeing initiatives.